The Effect of Financial Management Quality, Product Innovation, and Digital Marketing on Micro Business Growth in the Jakarta Culinary Sector - Sidrotun Naim (Westscience Press, 2024)
This research investigates the dynamics of micro-business growth in the Jakarta Culinary Sector, focusing on the impact of Financial Management Quality (FMQ), Product Innovation (PI), and Digital Marketing (DM). A quantitative analysis involving a sample of 150 micro businesses reveals compelling insights. Results indicate significant positive relationships between FMQ, PI, and DM with Micro Business Growth (MBG). The study emphasizes the pivotal role of sound financial practices, innovation, and digital marketing in fostering growth within the competitive culinary landscape of Jakarta. Findings contribute to the understanding of success factors in micro-businesses, offering practical implications for entrepreneurs and policymakers.